2009
DOI: 10.1093/cvr/cvp037
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A contributes to the cardiac dysfunction induced by endotoxemia

Abstract: AimsSepsis-associated cardiac dysfunction represents an intrinsic impairment of cardiomyocyte function due in part to a decrease in myofilament Ca2+ sensitivity associated with a sustained increase in cardiac troponin I (cTnI) phosphorylation at Ser23/24. Dephosphorylation of cTnI is under regulatory control. Thus, muscarinic and adenosine A1-receptor agonists antagonize β-adrenergic stimulation via activation of protein phosphatase 2A (PP2A). The aim of this study was to determine whether modulation of PP2A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
(59 reference statements)
2
23
0
Order By: Relevance
“…Hence, there seems to be a causal link between higher expression of PP2A C -B56␣, hypophosphorylation of myofilament proteins, and increased Ca 2ϩ sensitivity and contractile force. This is also supported by the fact that, on the other hand, an increased cTnI phosphorylation at Ser 23/24 and a decrease in myofilament Ca 2ϩ sensitivity in LPS-induced septic hearts was paralleled by a reduction in the expression of PP2A C -B56␣, resulting in an overall decreased PP2A activity (17). Taken together, these studies support the hypothesis that B56␣ is a crucial modulator of cardiac Ca 2ϩ sensitivity and contractility by influencing the PP2A-dependent dephosphorylation of regulatory myofilament proteins.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Hence, there seems to be a causal link between higher expression of PP2A C -B56␣, hypophosphorylation of myofilament proteins, and increased Ca 2ϩ sensitivity and contractile force. This is also supported by the fact that, on the other hand, an increased cTnI phosphorylation at Ser 23/24 and a decrease in myofilament Ca 2ϩ sensitivity in LPS-induced septic hearts was paralleled by a reduction in the expression of PP2A C -B56␣, resulting in an overall decreased PP2A activity (17). Taken together, these studies support the hypothesis that B56␣ is a crucial modulator of cardiac Ca 2ϩ sensitivity and contractility by influencing the PP2A-dependent dephosphorylation of regulatory myofilament proteins.…”
Section: Discussionmentioning
confidence: 70%
“…Analysis of myocardial fractions revealed that B56␣ was decreased in the myofilament fraction and increased in the cytosol after ␤-adrenergic stimulation by isoproterenol (ISO) (16). These dynamic changes in PP2A-B56␣ targeting may contribute to neurohumoral regulation of cardiac performance under physiological conditions and in the diseased heart, as demonstrated for sepsis-associated cardiac dysfunction (17).…”
mentioning
confidence: 96%
“…Similarly, we could not detect calmodulin kinase II cleavage in both in vivo and in vitro experiment settings. Implication of phosphatases in the development of sepsis-triggered cardiovascular dysfunction remains controversial (25,26). Here, we showed that PP2A activity is increased in SR vesicles isolated from endotoxin-treated rat hearts.…”
Section: Discussionmentioning
confidence: 84%
“…14 Previous study proved that LPS treatment represses PP2Ac expression and activity in myocardial cells. 15 Considering the tumor suppressive role of PP2A, we speculated that the inflammation-triggered PP2A inhibition participates in the inflammation-driven cancer progression.…”
Section: Introductionmentioning
confidence: 99%